Positive electrode material and preparation method thereof, and lithium battery
By covering the surface of LiNi0.5Co0.2Mn0.3O2 positive electrode material with ZrCl4 and performing high-valent metal ion doping modification, specific technical means are used to reduce the electron exchange resistance, and the problems of large K value and poor voltage holding capacity in the full-voltage high-voltage segment are solved, achieving the effect of voltage stability and small K value.
Patent Information
- Application Number
- CN202510077182.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-18
AI Technical Summary
Existing lithium batteries have problems such as large K value and poor voltage holding capacity during full-voltage high voltage period, resulting in a decrease in power storage capacity and frequent charging of electrical appliances, which makes the user experience poor.
By covering the surface of LiNi0.5Co0.2Mn0.3O2 material with ZrCl4 and undergoing high-valent metal ion doping modification, break exchange, exchange lithium free space effect and lithium ion-ion beam effect technology, the resistance during electron exchange is reduced and the positive electrode material is protected.
The voltage stability improvement and the reduction of the high voltage K value are achieved. The voltage of the battery is stable at more than 4.20V under full charge, and the K value is less than 1.5mV within 3 days, solving the problems of fast power outage and poor voltage holding capacity.
Smart Images

Figure HDA0005247440210000011 
Figure HDA0005247440210000012 
Figure HDA0005247440210000021
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and in particular to a positive electrode material and a preparation method thereof, and a lithium battery. Background Art
[0002] Lithium batteries are a type of battery that uses lithium metal as the positive / negative electrode material and a non-aqueous electrolyte solution. With the development of science and technology, lithium batteries have become mainstream.
[0003] The higher the voltage of a lithium battery, the greater its output power and the greater its ability to store electricity. Therefore, the higher the voltage, the better the performance of the lithium battery. However, in real life, when the battery is in the high-voltage section of full charge (4.15-4.23V), there is a large K value and poor pressure holding ability, which affects the power storage capacity. Electrical appliances equipped with the battery need to be charged frequently during use, which results in a poor experience. Therefore, the development of positive electrode materials with stable voltage and low high-voltage K value has become an urgent problem to be solved. Summary of the invention
[0004] In view of this, the present invention provides a positive electrode material and a preparation method thereof, as well as a lithium battery. The positive electrode material prepared by the present invention can improve voltage stability and reduce high voltage K value.
[0005] The present invention provides a method for preparing a positive electrode material, comprising the following steps:
[0006] A) LiNi 0.5 Co 0.2 Mn 0.3 O 2 dispersed in water to obtain a dispersion;
[0007] B) adding ZrCl to the dispersion under stirring and heating conditions 4 , to obtain a mixed solution;
[0008] C) adjusting the pH of the mixed solution to acidic, and spray drying to obtain a xerogel;
[0009] D) sintering the dry gel to obtain ZrCl 4 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 Material.
[0010] Preferably, in step B), the target temperature of the heating is 70-90°C.
[0011] Preferably, in step B), the target temperature of the heating is 80°C.
[0012] Preferably, in step B), ZrCl 4With step A) LiNi 0.5 Co 0.2 Mn 0.3 O 2 The mass ratio is (0.015~0.035)∶5.0.
[0013] Preferably, in step B), ZrCl 4 With step A) LiNi 0.5 Co 0.2 Mn 0.3 O 2 The mass ratio is 0.025:5.0.
[0014] Preferably, in step C), the pH of the mixed solution is adjusted to 4.8.
[0015] Preferably, in step C), the regulator used to adjust the pH value is an acrylic acid solution.
[0016] Preferably, in step D), the sintering comprises sequentially performing a first stage sintering and a second stage sintering;
[0017] in:
[0018] The sintering conditions in the first stage are: air atmosphere, temperature 250-350° C., time 5-6 h;
[0019] The conditions of the second stage sintering are: oxygen atmosphere, temperature 450-550° C., and time 8-9 hours.
[0020] The present invention also provides a positive electrode material prepared by the preparation method described in the above technical solution.
[0021] The present invention also provides a lithium battery, wherein the positive electrode active material is the ZrCl 4 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 Material.
[0022] The preparation method provided by the present invention comprises firstly 0.5 Co 0.2 Mn 0.3 O 2 dispersed in water to obtain a dispersion; then, ZrCl was added to the dispersion under stirring and heating conditions. 4 , obtaining a mixed solution; then adjusting the pH of the mixed solution to acidic, spray drying, obtaining a dry gel; and finally sintering the dry gel to obtain ZrCl 4 Coated LiNi 0.5 Co 0.2 Mn 0.3O 2 The method of the present invention realizes LiNi 0.5 Co 0.2 Mn 0.3 O 2 The surface coating of the material and the doping modification of high-valent metal ions can reduce the resistance of electron exchange through three aspects: break exchange (BCE), exchange lithium free space effect (ESSE) and lithium ion-ion beam effect (LIPSE), reduce the loss of the battery and protect the positive electrode material from oxidation, corrosion and other harmful factors, thereby reducing the self-discharge of the battery and reducing the K value. The BCE process can significantly reduce the surface of the positive electrode material to Li + The charge density of ESSE can reduce the resistance of electron exchange. + Enter the local area of the cathode material, allowing them to participate in electron exchange more efficiently; LIPSE technology can inhibit Li + deposition, preventing the corrosion of the positive electrode material and facilitating the + Maintain the best charge. The structural stability and charge-discharge performance of the electrode material can be optimized by doping with high-valent metal ions. Therefore, the present invention improves the material stability by coating the surface of the high-voltage K-value positive electrode material and doping with high-valent metal ions, effectively solving the problem of fast power loss and poor pressure holding ability of the battery when fully charged.
[0023] The test results show that the voltage of the high-voltage K-value positive electrode material is stable at above 4.20V for 30 days, and the K value is less than 1.5mV within 3 days. It achieves the effect of voltage stability and small high-voltage K value, and effectively solves the problems of fast power loss and poor voltage maintenance ability of the battery when fully charged. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0025] Figure 1 LiNi 0.5 Co 0.2 Mn 0.3 O 2 Materials and Example 1 and Comparative Examples 1-3 obtained by ZrCl 4 , CuCl 2 、Al 2 O 3 , Fe 2 O 3 Coated LiNi0.5 Co 0.2 Mn 0.3 O 2 XRD spectrum of the material;
[0026] Figure 2 LiNi 0.5 Co 0.2 Mn 0.3 O 2 Materials and Example 1 and Comparative Examples 1-3 obtained by ZrCl 4 , CuCl 2 、Al 2 O 3 , Fe 2 O 3 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 FT-IR spectrum of the material; among them, Figure 2 (a) LiNi 0.5 Co 0.2 Mn 0.3 O 2 FT-IR spectrum of the material, Figure 2 (b) ZrCl 4 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 FT-IR spectrum of the material, Figure 2 (c) CuCl 2 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 FT-IR spectrum of the material, Figure 2 (d) is Al 2 O 3 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 FT-IR spectrum of the material, Figure 2 (e) is Fe 2 O 3 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 FT-IR spectrum of the material;
[0027] Figure 3 LiNi 0.5 Co 0.2 Mn 0.3 O2 Materials and Example 1 and Comparative Examples 1-3 obtained by ZrCl 4 , CuCl 2 、Al 2 O 3 , Fe 2 O 3 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 SEM image of the material; among them, Figure 3 (a) is the ZrCl obtained in Example 1 4 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 SEM images of the materials, Figure 3 (b) is the CuCl obtained in Comparative Example 1 2 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 SEM images of the materials, Figure 3 (c) is the Al obtained in Comparative Example 2 2 O 3 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 SEM images of the materials, Figure 3 (d) is the Fe obtained in Comparative Example 3 2 O 3 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 SEM images of materials;
[0028] Figure 4 LiNi 0.5 Co 0.2 Mn 0.3 O 2 Materials and Example 1 and Comparative Examples 1-3 obtained by ZrCl 4 , CuCl 2 、Al 2 O 3 , Fe 2 O 3 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 TEM image of the material; among them, Figure 4 (a) is the ZrCl obtained in Example 1 4Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 TEM images of the materials, Figure 4 (b) is the CuCl obtained in Comparative Example 1 2 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 TEM images of the materials, Figure 4 (c) is the Al obtained in Comparative Example 2 2 O 3 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 TEM images of the materials, Figure 4 (d) is the Fe obtained in Comparative Example 3 2 O 3 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 TEM images of the materials;
[0029] Figure 5 This is a comparison chart of the voltage curve of the high-voltage section at full charge of 4.23V;
[0030] Figure 6 This is a comparison chart of the K value curve of the high-voltage section with a full charge of 4.23V. DETAILED DESCRIPTION
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0032] In this article, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0033] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.
[0034] Herein, when it comes to numerical ranges, unless otherwise specified, the numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0035] In this article, when referring to the units of a data range, if only the right endpoint is followed by a unit, it means that the units of the left and right endpoints are the same.
[0036] The present invention provides a method for preparing a positive electrode material, comprising the following steps:
[0037] A) LiNi 0.5 Co 0.2 Mn 0.3 O 2 dispersed in water to obtain a dispersion;
[0038] B) adding ZrCl to the dispersion under stirring and heating conditions 4 , to obtain a mixed solution;
[0039] C) adjusting the pH of the mixed solution to acidic, and spray drying to obtain a xerogel;
[0040] D) sintering the dry gel to obtain ZrCl 4 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 Material.
[0041] [About Step A]:
[0042] A) LiNi 0.5 Co 0.2 Mn 0.3 O 2 Dispersed in water to obtain a dispersion.
[0043] In the present invention, the LiNi 0.5 Co 0.2 Mn 0.3 O 2 The material is a ternary positive electrode material, and its source is not particularly limited. It can be a commercial product or prepared according to a preparation method known in the art.
[0044] In the present invention, the water is preferably deionized water.
[0045] In the present invention, the LiNi0.5 Co 0.2 Mn 0.3 O 2 The usage ratio of the polyol to water is preferably 5.0 g: (200-300) mL, more preferably 5.0 g: 250 mL.
[0046] In the present invention, step A) preferably specifically comprises: 0.5 Co 0.2 Mn 0.3 O 2 Add to water, stir, and let stand to obtain a dispersion. The stirring speed is preferably 2000-4000 rpm, specifically 2000 rpm, 2500 rpm, 3000 rpm, 3500 rpm, 4000 rpm; the stirring time is preferably 60-120 min, specifically 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min. By stirring, LiNi 0.5 Co 0.2 Mn 0.3 O 2 and mixing with water. After the above stirring, the mixture is allowed to stand for preferably 1 to 3 hours, specifically 1 hour, 2 hours, 3 hours, and more preferably 2 hours. After standing, a dispersion is obtained.
[0047] [About step B]:
[0048] B) adding ZrCl to the dispersion under stirring and heating conditions 4 , to obtain a mixed solution.
[0049] In the present invention, the dispersion obtained in step A) is stirred and heated. The stirring speed is preferably 2000-4000 rpm, specifically 2000 rpm, 2500 rpm, 3000 rpm, 3500 rpm, 4000 rpm. The target temperature of the heating is preferably 70-90°C, specifically 70°C, 75°C, 80°C, 85°C, 90°C, more preferably 80°C. After the dispersion obtained in step A) is stirred and heated to the target temperature, ZrCl is added under the above conditions. 4 After the addition is completed, the above stirring and target temperature conditions are maintained for a certain period of time, preferably 1 to 2 hours, specifically 1 hour, 1.5 hours, 2 hours, to obtain a mixed solution. Alternatively, the dispersion obtained in step A) is stirred and heated to the target temperature, and ZrCl is added during the above process. 4 After the addition is completed, the above stirring and target temperature conditions are maintained for a certain period of time, preferably 1 to 3 hours, specifically 1 hour, 2 hours, 3 hours, to obtain a mixed solution.
[0050] In the present invention, the ZrCl 4 With step A) LiNi 0.5 Co 0.2 Mn 0.3 O 2 The mass ratio is preferably (0.015-0.035):5.0, specifically 0.015:5.0, 0.020:5.0, 0.025:5.0, 0.030:5.0, 0.035:5.0, and more preferably 0.025:5.0.
[0051] [About Step C]:
[0052] C) adjusting the pH of the mixed solution to acidic, and spray drying to obtain a xerogel.
[0053] In the present invention, after obtaining the mixed solution in step B), an acidic regulator is added to adjust the pH of the mixed solution to acidity. In the present invention, the regulator used to adjust the pH value is preferably an acrylic acid solution. In the present invention, the pH is adjusted to acidity, preferably to 4.8. In the present invention, after adjusting the pH, the temperature is lowered, preferably to room temperature. Then spray drying is performed to obtain a xerogel.
[0054] [About Step D]:
[0055] D) sintering the dry gel to obtain ZrCl 4 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 Material.
[0056] In the present invention, the sintering includes sequentially performing a first stage sintering and a second stage sintering.
[0057] in:
[0058] The first stage is preferably sintered under the following conditions: air atmosphere, temperature 250-350°C, time 5-6h. The temperature may be 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, more preferably 300°C. The time may be 5h, 5.5h, 6h, more preferably 5h.
[0059] The conditions of the second stage sintering are preferably: oxygen atmosphere, temperature 450-550°C, time 8-9h. The temperature may be 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, more preferably 500°C. The time may be 8h, 8.5h, 9h, more preferably 8h. The volume percentage of oxygen in the oxygen atmosphere is ≥5%.
[0060] After the above sintering treatment, ZrCl 4 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 Material.
[0061] The present invention also provides a ZrCl prepared by the preparation method described in the above technical solution. 4 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 Material.
[0062] The present invention also provides a lithium battery, wherein the positive electrode active material is the ZrCl 4 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 Material.
[0063] The above preparation method of the present invention realizes LiNi 0.5 Co 0.2 Mn 0.3 O 2 The surface coating of the material and the doping modification of high-valent metal ions can reduce the resistance of electron exchange through three aspects: break exchange (BCE), exchange lithium free space effect (ESSE) and lithium ion-ion beam effect (LIPSE), reduce the loss of the battery and protect the positive electrode material from oxidation, corrosion and other harmful factors, thereby reducing the self-discharge of the battery and reducing the K value. The BCE process can significantly reduce the surface of the positive electrode material to Li + The charge density of ESSE can reduce the resistance of electron exchange. + Enter the local area of the cathode material, allowing them to participate in electron exchange more efficiently; LIPSE technology can inhibit Li + deposition, preventing the corrosion of the positive electrode material and facilitating the +Maintain the best charge. The structural stability and charge-discharge performance of the electrode material can be optimized by doping with high-valent metal ions. Therefore, the present invention improves the material stability by coating the surface of the high-voltage K-value positive electrode material and doping with high-valent metal ions, effectively solving the problem of fast power loss and poor pressure holding ability of the battery when fully charged.
[0064] The test results show that the voltage of the high-voltage K-value positive electrode material is stable at above 4.20V for 30 days, and the K value is less than 1.5mV within 3 days.
[0065] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0066] Example 1
[0067] A) Take 5.0g of LiNi 0.5 Co 0.2 Mn 0.3 O 2 The material was added into 250 mL of deionized water, stirred at 3000 rpm for 60 min using a stirrer, and then allowed to stand for 2 h to obtain a dispersion.
[0068] B) The dispersion obtained in step A) was stirred (at a speed of 3000 rpm) and heated to 80°C. During the above process, 0.025 g of ZrCl 4 After the addition is completed, the mixture is maintained under the above conditions for 2 h to obtain a mixed solution.
[0069] C) adding acrylic acid solution to the mixed solution obtained in step B), adjusting the pH value to 4.8, cooling, and spray drying to obtain a xerogel.
[0070] D) The dry gel obtained in step C) was first sintered in an air atmosphere at 300°C for 5 h, and then sintered in an oxygen atmosphere at 500°C for 8 h to obtain ZrCl 4 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 Material.
[0071] Comparative Example 1
[0072] The method is implemented according to Example 1, except that the ZrCl in step B) is replaced by 4 Replaced by CuCl 2 , finally CuCl 2 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2Material.
[0073] Comparative Example 2
[0074] A) Same as Example 1.
[0075] B') Add 0.1 g of Al(NO 3 )·6H 2 O, stirred at 3000 rpm for 2 h to obtain a mixed solution.
[0076] C') adding aqueous ammonia to the mixed solution obtained in step B') to adjust the pH value to 4.8, and solid precipitates. The solid is filtered off and washed with deionized water and dried under vacuum at 80° C. for 4 h to obtain a solid.
[0077] D') The solid obtained in step C') was heat treated in a muffle furnace at 480°C for 8h to obtain Al 2 O 3 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 Material.
[0078] Comparative Example 3
[0079] The method is implemented according to Comparative Example 2, except that 0.1 g of Al(NO 3 )·6H 2 O is replaced by 0.16 g of Fe 2 (SO 4 )·18H 2 O, and finally Fe 2 O 3 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 Material.
[0080] Product Testing :
[0081] (1) XRD test
[0082] The material structure of the material was determined using a Japanese D / Max-2200 X-ray powder diffractometer with CuKa as the radiation source, a scanning range of 12°-85°, a tube current of 28 mA, and a tube voltage of 35 kV.
[0083] Figure 1 LiNi 0.5 Co 0.2 Mn 0.3 O 2 The material (ie, NCM) and the ZrCl obtained in Example 1 and Comparative Examples 1-34 , CuCl 2 、Al 2 O 3 , Fe 2 O 3 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 XRD spectrum of the material. The diffraction peaks of the five samples in the spectrum are sharp and high, all belonging to α-NaFeO 2 The characteristic peaks of the layered structure, and the XRD spectra of all materials are almost the same, without other diffraction peaks. 4 , CuCl 2 、Al 2 O 3 , Fe 2 O 3 No LiNi 0.5 Co 0.2 Mn 0.3 O 2 The crystal structure of the material has a significant effect, which only covers the surface of the material.
[0084] (2) Infrared spectroscopy
[0085] Nicolet AVA-TAR360 infrared spectrometer was used to observe the functional groups of the coating materials and conduct FT-IR phase analysis. The test range was 4500-450cm -1 , resolution 3cm -1 FT-IR spectra are mainly used to analyze the chemical bonds and structural information of functional groups on the surface of materials, and can provide detailed information about the chemical composition and interactions of the material surface.
[0086] Figure 2 It is LiNi 0.5 Co 0.2 Mn 0.3 O 2 Materials and Example 1 and Comparative Examples 1-3 obtained by ZrCl 4 , CuCl 2 、Al 2 O 3 , Fe 2 O 3 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 Fourier transform infrared spectroscopy (FT-IR) spectrum of the material; Curve A is LiNi 0.5 Co 0.2 Mn 0.3 O 2FT-IR spectrum of the material, curve B is the ZrCl 4 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 FT-IR spectrum of the material, curve C is the CuCl 2 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 FT-IR spectrum of the material, curve D is the Al 2 O 3 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 FT-IR spectrum of the material, curve E is the Fe 2 O 3 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 FT-IR spectra of the materials.
[0087] Curve A--LiNi 0.5 Co 0.2 Mn 0.3 O 2 Materials: As a control, LiNi 0.5 Co 0.2 Mn 0.3 O 2 The FT-IR spectrum of a material will show its unique chemical bond vibration peaks, such as the vibration peak of the metal-oxygen bond (MO). The position and intensity of these characteristic peaks can be used as a reference for determining the basic structure of the material.
[0088] Curve B--ZrCl 4 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 Materials: In the FT-IR spectrum, ZrCl 4 The appearance of these characteristic peaks indicates that ZrCl 4 Successfully coated on LiNi 0.5 Co 0.2 Mn 0.3 O 2 The surface of the material, and the chemical bond structure of the coating layer is relatively stable. 4 The existence of coating layer has an important effect on LiNi 0.5 Co 0.2 Mn0.3 O 2 Some characteristic peaks of the material have a certain impact, such as a slight shift in peak position or a change in peak intensity, which may be due to the interaction between the coating layer and the matrix material.
[0089] Curve C--CuCl 2 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 Material: The FT-IR spectrum shows the vibration peaks of Cu-O bond and Cu-Cl bond. These characteristic peaks indicate that CuCl 2 The presence of coating layer. 4 Compared with the coated materials, CuCl 2 The characteristic peaks of the coating layer are more obvious, and for LiNi 0.5 Co 0.2 Mn 0.3 O 2 The material characteristic peak has a greater impact, which may be due to the CuCl 2 With LiNi 0.5 Co 0.2 Mn 0.3 O 2 The interaction between materials is strong, resulting in relatively poor chemical stability of the coating.
[0090] Curve D--Al 2 O 3 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 Material: In the FT-IR spectrum, the vibration peaks of Al-O bonds appear. These characteristic peaks indicate that Al 2 O 3 The presence of coating layer. 2 O 3 The characteristic peaks of the coating layer are 0.5 Co 0.2 Mn 0.3 O 2 The characteristic peaks of the material have a certain influence, but the degree of influence is between ZrCl 4 and CuCl 2 Between the coated materials, this indicates that Al 2 O 3 The coating has good chemical stability, but moderate interaction with the matrix material.
[0091] Curve E--Fe 2 O 3 Coated LiNi 0.5 Co0.2 Mn 0.3 O 2 Material: The FT-IR spectrum shows the vibration peaks of Fe-O bonds. These characteristic peaks indicate that Fe 2 O 3 The presence of coating layer. 2 O 3 The characteristic peaks of the coating layer are 0.5 Co 0.2 Mn 0.3 O 2 The characteristic peaks of the material have a greater impact, and the intensity of the characteristic peaks is stronger, which may be due to Fe 2 O 3 With LiNi 0.5 Co 0.2 Mn 0.3 O 2 The strong interaction between materials results in poor chemical stability of the coating layer, which is easily affected by the external environment.
[0092] By analyzing the FT-IR spectra of different coating materials, we can understand the chemical composition and structural characteristics of the coating layer, as well as the interaction between the coating layer and the matrix material, so as to evaluate the coating layer on LiNi 0.5 Co 0.2 Mn 0.3 O 2 Influence of material properties.
[0093] (3) SEM characterization
[0094] A Supra55 field emission scanning electron microscope produced by Zeiss of Germany was used with an accelerating voltage of 12 kV to observe the surface morphology of the samples.
[0095] Figure 3 The ZrCl 4 , CuCl 2 、Al 2 O 3 , Fe 2 O 3 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 SEM image of the material; among them, Figure 3 (a) is the ZrCl obtained in Example 1 4 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 SEM images of the materials, Figure 3 (b) is the CuCl obtained in Comparative Example 12 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 SEM images of the materials, Figure 3 (c) is the Al obtained in Comparative Example 2 2 O 3 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 SEM images of the materials, Figure 3 (d) is the Fe obtained in Comparative Example 3 2 O 3 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 SEM image of the material. It can be seen that ZrCl 4 The particle size of the coated material surface is smaller, and the distribution is more uniform and dense, without agglomeration. 2 、Al 2 O 3 , Fe 2 O 3 Although a layer of coating material is attached to the surface of the coated material, the particles are of different sizes, the coating layer is uneven, and particles may agglomerate locally.
[0096] (4) TEM characterization
[0097] A JEM2100 transmission electron microscope was used to observe the submicrostructure and ultrastructure of the coating material and characterize the protective degree of the coating material. Test: First, ultrasonically disperse the sample in anhydrous ethanol, let it stand for 12 minutes, extract the sample using a microinjector and drop it on a copper mesh, and test it after drying. TEM images are usually used to observe the submicrostructure and ultrastructure of materials, which can reveal the microscopic morphology, grain size, grain boundary distribution of the material, and the thickness and uniformity of the coating layer.
[0098] Figure 4 The ZrCl 4 , CuCl 2 、Al 2 O 3 , Fe 2 O 3 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 TEM image of the material; among them, Figure 4 (a) is the ZrCl obtained in Example 1 4 Coated LiNi0.5 Co 0.2 Mn 0.3 O 2 TEM images of the materials, Figure 4 (b) is the CuCl obtained in Comparative Example 1 2 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 TEM images of the materials, Figure 4 (c) is the Al obtained in Comparative Example 2 2 O 3 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 TEM images of the materials, Figure 4 (d) is the Fe obtained in Comparative Example 3 2 O 3 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 TEM image of the material.
[0099] Figure 4 (a)--ZrCl 4 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 Material: TEM images show that the particle size of the material is small, and the distribution is uniform and dense, without obvious agglomeration. The thickness of the coating layer is relatively uniform, and the interface between it and the base material is clear, indicating that ZrCl 4 The coating layer can cover the LiNi well. 0.5 Co 0.2 Mn 0.3 O 2 Material surface, providing good protection.
[0100] Figure 4 (b)--CuCl 2 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 Material: ZrCl 4 Compared with the coated materials, CuCl 2 The coated material shows a large particle size in the TEM image, and the distribution is not uniform, and there is a certain degree of agglomeration. The thickness of the coating layer is uneven, and some areas are thicker or thinner, and the interface between the coating layer and the base material may not be clear, indicating that CuCl 2The protective effect of the coating is relatively poor.
[0101] Figure 4 (c)--Al 2 O 3 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 Material: TEM images show that the particle size of the material is between ZrCl 4 and CuCl 2 The distribution of the coated materials is relatively uniform, but there is still a small amount of agglomeration. The thickness of the coating layer is relatively uniform, but there are some defects or discontinuities at the interface with the base material, indicating that Al 2 O 3 The protective effect of the cladding is acceptable, but there is still room for improvement.
[0102] Figure 4 (d)--Fe 2 O 3 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 Material: In the TEM image, the particle size of the material is large, the distribution is uneven, and the agglomeration phenomenon is obvious. The thickness of the coating layer is uneven, and some areas are thicker or thinner. The interface between the coating layer and the base material is not clear, and there are even some gaps or cracks. This indicates that Fe 2 O 3 The protective effect of the coating is poor, which can easily lead to a decrease in material performance.
[0103] By comparing the TEM images of different coating materials, we can intuitively understand the effects of various coating layers on LiNi 0.5 Co 0.2 Mn 0.3 O 2 The influence of material microstructure can be used to evaluate its performance and stability in practical applications.
[0104] (5) Electrochemical performance test
[0105] Battery production: The positive electrode material, acetylene black conductive agent, and PVDF binder were mixed in a mass ratio of 75:15:10, and N-methylpyrrolidone solvent (NMP) was used as a dispersant. The mixture was ball-milled and coated on aluminum foil. The positive electrode was dried at 85°C to obtain the positive electrode. 6The electrolyte (concentration 1 mol / L, solvent is a mixed solvent of EC:DMC with a volume ratio of 1:1) was used to assemble CR2025 button cells in an argon atmosphere glove box. A control group battery was made with lithium phosphate as the positive electrode material and the same operation was performed.
[0106] The battery was subjected to constant current charge and discharge tests using a LANDCT2001A electrochemical workstation with a voltage range of 3.5-4.5 V and a rate of 0.2C.
[0107] Figure 5 This is a comparison chart of the voltage curve of the high-voltage section with a full charge of 4.23V. Figure 6 This is a comparison of the K value curves of the high-voltage section at full charge of 4.23V. In the figure, the "high-voltage K value positive electrode material" line represents the battery assembled with the positive electrode material obtained in Example 1, and the "conventional product" line represents the battery assembled with the lithium phosphate positive electrode material. It can be seen that the ZrCl obtained in Example 1 4 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 The voltage of the positive electrode battery of the material is stable at above 4.20V for 30 days, and the K value is less than 1.5mV within 3 days, which achieves the effect of voltage stability and low high voltage K value.
[0108] In summary, the ZrCl prepared by the present invention 4 Coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 Materials, after coating, LiNi 0.5 Co 0.2 Mn 0.3 O 2 The crystal structure of the material has a significant impact, the surface of the material can still maintain a good crystal structure, and ZrCl 4 The particles on the surface of the coated material are small in size, evenly distributed, dense, and free of agglomeration. In actual applications, the voltage is stable at above 4.20V for 30 days, and the K value is less than 1.5mV within 3 days. It achieves the effect of voltage stability and low high-voltage K value, effectively solving the problems of fast power loss and poor voltage maintenance when the battery is fully charged.
[0109] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. A method for preparing a positive electrode material, characterized in that: The following steps are involved: A) LiNi 0.5 Co 0.2 Mn 0.3 O2 is dispersed in water to obtain a dispersion; B) adding ZrCl4 to the dispersion under stirring and heating conditions to obtain a mixed solution; C) adjusting the pH of the mixed solution to acidic, and spray drying to obtain a xerogel; D) sintering the dry gel to obtain ZrCl4-coated LiNi 0.5 Co 0.2 Mn 0.3 O2 material.
2. The preparation method according to claim 1, characterized in that: In step B), the target temperature of the heating is 70-90°C.
3. The preparation method according to claim 1 or 2, characterized in that: In step B), the target temperature of the heating is 80°C.
4. The preparation method according to claim 1, characterized in that: ZrCl4 in step B) and LiNi in step A) 0.5 Co 0.2 Mn 0.3 The mass ratio of O2 is (0.015~0.035)∶5.
0.
5. The preparation method according to claim 1 or 4, characterized in that: ZrCl4 in step B) and LiNi in step A) 0.5 Co 0.2 Mn 0.3 The mass ratio of O2 is 0.025:5.
0.
6. The preparation method according to claim 1, characterized in that: In step C), the pH of the mixed solution is adjusted to 4.
8.
7. The preparation method according to claim 1, characterized in that: In step C), the regulator used to adjust the pH value is an acrylic acid solution.
8. The preparation method according to claim 1, characterized in that: In step D), the sintering includes sequentially performing a first stage sintering and a second stage sintering; in: The sintering conditions in the first stage are: air atmosphere, temperature 250-350° C., time 5-6 h; The conditions of the second stage sintering are: oxygen atmosphere, temperature 450-550° C., and time 8-9 hours.
9. A positive electrode material obtained by the preparation method according to any one of claims 1 to 8.
10. A lithium battery, characterized in that: The positive electrode active material is the ZrCl4-coated LiNi 0.5 Co 0.2 Mn 0.3 O2 material.